Antibacterial Activity of the Vegetable Extract from Chestnut (Castanea mollissima Blume) Shell - Wang, L.W.; Zhao , B. (Asian Journal of Chemistry, 2011)
The vegetable extract obtained from the aqueous acetone solution of chestnut (Castanea mollissima Blume) shell was screened for its antimicrobial activity. The extract showed a wide spectrum of antibacterial activities against tested gram-positive and gram-negative bacteria.